A Narrow pH Range Supports Butanol, Hexanol, and Octanol Production from Syngas in a Continuous Co-culture of Clostridium ljungdahlii and Clostridium kluyveri with In-Line Product Extraction - Richter, Hanno; Molitor, Bastian; Diender, Martijn; Sousa, Diana Z.; Angenent, Largus T. (Frontiers in Microbiology, 2016)
Carboxydotrophic bacteria (CTB) have received attention due to their ability to synthesize commodity chemicals from producer gas and synthesis gas (syngas). CTB have an important advantage of a high product selectivity compared to chemical catalysts. However, the product spectrum of wild-type CTB is narrow. Our objective was to investigate whether a strategy of combining two wild-type bacterial strains into a single, continuously fed bioprocessing step would be promising to broaden the product spectrum. Here, we have operated a syngas-fermentation process with Clostridium ljungdahlii and Clostridium kluyveri with in-line product extraction through gas stripping and product condensing within the syngas recirculation line. The main products from C. ljungdahlii fermentation at a pH of 6.0 were ethanol and acetate at net volumetric production rates of 65.5 and 431 mmol C•L-1•d-1, respectively. An estimated 2/3 of total ethanol produced was utilized by C. kluyveri to chain elongate with the reverse β-oxidation pathway, resulting in n-butyrate and n-caproate at net rates of 129 and 70 mmol C•L-1•d-1, respectively. C. ljungdahlii likely reduced the produced carboxylates to their corresponding alcohols with the reductive power from syngas. This resulted in the longer-chain alcohols n-butanol, n-hexanol, and n-octanol at net volumetric production rates of 39.2, 31.7, and 0.045 mmol C•L-1•d-1, respectively. The continuous production of the longer-chain alcohols occurred only within a narrow pH spectrum of 5.7-6.4 due to the pH discrepancy between the two strains. Regardless whether other wild-type strains could overcome this pH discrepancy, the specificity (mol carbon in product per mol carbon in all other liquid products) for each longer-chain alcohol may never be high in a single bioprocessing step. This, because two bioprocesses compete for intermediates (i.e., carboxylates): 1) chain elongation; and 2) biological reduction. This innate competition resulted in a mixture of n-butanol and n-hexanol with traces of n-octanol.